ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL MANAGEMENT BEHAVIOR PADA UMKM DI KOTA KENDARI - Ainun Ardianti Hilyatul A; Dedy Takdir Syaifuddin; Nuryamin Budi; Velentinus Amstrong; Farhan Ramdhani Istianandar; Unika Oktaviani Damau (Jurusan Manajemen FEB UHO, 2024)
The purpose of this research is to determine factors such as financial knowledge, financial planning, internal locus of control, financial self-efficacy, financial experience, and personality influence the financial management behavior of MSME actors in Kendari City. This research is quantitative research with data collection techniques using questionnaires. The sample used amounted to 96 people distributed to all MSME actors in Kendari City from various MSME sectors. This research uses non-probability sampling technique with accidental sampling. The data analysis technique in this research uses inferential statistical analysis with the help of Smart PLS by conducting several stages of testing the outer model and the inner model. The results of the study show that financial knowledge, financial planning, internal locus of control, financial self-efficacy, financial experience, and personality have a positive and significant effect on the financial management behavior of MSME actors in Kendari City. This is evidenced by the path estimation values for the variables financial knowledge, financial planning, financial self-efficacy, financial experience, and personality, where the path estimation values are positive. Meanwhile, the variable internal locus of control has a negative and insignificant effect on financial management behavior.